THE RELATIONSHIP BETWEEN COMPETITION ENVIRONMENT AND QUALITY OF SERVICES: A MICROECONOMIC ANALYSIS OF THE ACTIVITIES OF SERVICE ENTERPRISES (Web of Discoveries: Journal of Analysis and Inventions, 2026)
In this scientific article the relationship between the competitive environment and the quality of services in the service market is analyzed from a microeconomic approach. The level of competition between firms in the service market has a direct impact not only on price policy, but also on service quality, innovation and consumer satisfaction. The study conducts a theoretical analysis based on market structure, service differentiation, demand elasticity, and profit maximization model. It is also substantiated that the increase in the quality of service is the main factor forming the competitive advantage.